Research and Development Evolving Trends and Practices Towards Human, Institutional and Economic Sectors Growth - Maad, Soha (IntechOpen, 2017)
This book traces the evolution and trends in research and development (R&D) and sheds light on key R&D practices of vital importance for human, institutional, and economic sector growth. Following an introductory chapter, gathering a pool of knowledge about R&D, the subsequent book chapters are classified into three sections: (1) "R&D for human growth and prosperity" with particular focus on human development and research-development-extension relationships, (2) "R&D for institutional growth" with particular focus on small- and medium-sized enterprises (SMEs), and (3) "R&D for economic sector growth" with particular focus on smart microgrids, energy consumption and greenhouse gas emission, and metallurgical industry. Target readers of this book are various economic stakeholders including academia, industry, investors, and public sector entities. Given its transdisciplinary coverage of various areas in research and development, this book fills a knowledge gap and motivates research and innovation among academia, industry, and public sector.